THE THE IMPACT OF E-COMMERCE ON THE GROWTH OF YOUNG ENTREPRENEURSHIP: LITERATURE REVIEW - Widiari, Putu Ayu Ossi; Wulandari, Putu Riska; Kristina, Ni Made Rai; Premananda, Luh Putu Uttari; Krisdayanthi, Astrid; Trisnayanti, Komang Rika (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
E-commerce plays an essential role in supporting young entrepreneurs by providing easier access to markets, lower business costs, and wider opportunities for innovation. However, there is still a gap between theories of digital entrepreneurship and real practices, as many young entrepreneurs face challenges such as limited digital literacy, funding, and business management skills. This study aims to analyze how e-commerce influences the growth and sustainability of young entrepreneurship and to identify the main factors that support or hinder their success. Using a systematic literature review based on PRISMA guidelines, this research reviewed studies published between 2015 and 2024 from Scopus, ScienceDirect, and Google Scholar. The analysis used three main theories: Entrepreneurial Opportunity Recognition Theory, Technology Acceptance Model, and Resource-Based View. The findings show that e-commerce not only serves as a platform for transactions but also as an ecosystem for learning and innovation. It helps young entrepreneurs recognize opportunities, adopt technology, and manage resources more effectively. However, strengthening digital education, access to finance, and policy support is needed to ensure the sustainability of youth entrepreneurship in the digital era.